Analisis Tiger Parenting bagi Perkembangan Emosional Anak - Umi Salma Fauziyah; Maemonah Maemonah (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The purpose of this study was to determine the impact of applying tiger parenting style for children's emotional development. This research is a type of library research whose main source comes from research related to this research, both from scientific work, research results, books, and additional data sources derived from observations. The parenting style analyzed is the tiger parenting style. From the parenting style analyzed, the results show that emotional development in particular has more negative effects than positive effects such as children being unhappy, rarely having fun, sad because they are constantly being pressured, feeling lacking authority in their own lives because everything continues to be directed by parents , until the worst is the symptoms of depression.